2021
DOI: 10.1016/j.celrep.2021.109056
|View full text |Cite
|
Sign up to set email alerts
|

KSHV infection drives poorly cytotoxic CD56-negative natural killer cell differentiation in vivo upon KSHV/EBV dual infection

Abstract: KSHV infection drives poorly cytotoxic CD56negative natural killer cell differentiation in vivo upon KSHV/EBV dual infection Graphical abstract Highlights d CD56 -CD16 + NK cells accumulate upon KSHV/EBV dual infection in humanized mice d KSHV titers correlate with CD56 -CD16 + NK cell frequency in vivo d CD56 -CD16 + NK cells display impaired effector functions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 87 publications
(129 reference statements)
0
32
0
1
Order By: Relevance
“…This co-infection can be frequently found in primary effusion lymphoma (PEL) that is 100% associated with KSHV and, in the majority of cases (90%), also harbors EBV [ 127 , 132 , 133 ]. More recently, it was also found that EBV infection supports persistent KSHV infection both in humanized mice [ 131 , 134 ] and in vitro [ 130 , 135 ]. Consistent with these findings are the observations that KSHV is usually not found without EBV co-infection in African children [ 136 , 137 ], and that the monkey orthologs of these viruses can be co-transmitted in macaques [ 138 ].…”
Section: Role Of Co-infections On Ebv Infection Immune Control and Oncogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…This co-infection can be frequently found in primary effusion lymphoma (PEL) that is 100% associated with KSHV and, in the majority of cases (90%), also harbors EBV [ 127 , 132 , 133 ]. More recently, it was also found that EBV infection supports persistent KSHV infection both in humanized mice [ 131 , 134 ] and in vitro [ 130 , 135 ]. Consistent with these findings are the observations that KSHV is usually not found without EBV co-infection in African children [ 136 , 137 ], and that the monkey orthologs of these viruses can be co-transmitted in macaques [ 138 ].…”
Section: Role Of Co-infections On Ebv Infection Immune Control and Oncogenesismentioning
confidence: 99%
“…Consistent with these findings are the observations that KSHV is usually not found without EBV co-infection in African children [ 136 , 137 ], and that the monkey orthologs of these viruses can be co-transmitted in macaques [ 138 ]. Moreover, co-infection of EBV with KSHV in humanized mice causes increased lymphoma formation, and the emerging lymphomas display some features of plasma cell differentiation [ 131 , 134 ] which is characteristic for PELs [ 133 ]. These PEL-like tumors have an elevated reactivation of EBV to its lytic replication ( Figure 2 C).…”
Section: Role Of Co-infections On Ebv Infection Immune Control and Oncogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Both EBV- and KSHV-encoded miRNAs compromise MICB expression [ 126 ], while K5 of KSHV ubiquitinates both MICA and MICB for internalization and degradation [ 127 ]. Thus, both viruses seem to compromise NK cell recognition, even so their co-infection leads to the differentiation of CD56-negative NK cells with poor function [ 128 ].…”
Section: Manipulation Of Antigen Presentation and Immune Recognition By Ebv And Kshvmentioning
confidence: 99%